1999
DOI: 10.1046/j.1442-2042.1999.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical finding of α‐1‐antichymotrypsin in tissues of benign prostatic hyperplasia and prostate cancer

Abstract: Background: Ratio of free to total (F/T) prostate-specific antigen (PSA) is higher in the blood of patients with benign prostatic hyperplasia than those with prostate cancer. To clarify the difference between ratios in these two, a-1-antichymotrypsin, the major component of the bound PSA in the blood, was immunohistochemically examined. Methods: Tissues were obtained surgically via a retropubic approach from patients with benign prostatic hyperplasia (nine cases) and prostate cancer (27 cases). These samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…4). ACT appears to be produced in small amounts in normal and BPH tissue, and in much higher amounts by prostate cancer cells [37–40]. In addition, Miller et al.…”
Section: Molecular Forms Of Psa In Human Serummentioning
confidence: 99%
“…4). ACT appears to be produced in small amounts in normal and BPH tissue, and in much higher amounts by prostate cancer cells [37–40]. In addition, Miller et al.…”
Section: Molecular Forms Of Psa In Human Serummentioning
confidence: 99%
“…Supposing cancer cells are the main source of α‐1‐antichymotrypsin in the tissues, the F/T ratio in serum might not correlate with the ratio of α‐1‐antichymotrypsin‐stained cancer cells the entire cancer cell population. However, no relationship was noticed, 22 therefore, regulation of the F/T ratio still remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…21 Using an immunohistochemical technique we also found a-1-antichymotrypsin-stained cancer cells in the prostate, but there was only a few similarly stained glandular cells in the tissues of patients with benign prostatic hyperplasia. 22 Moreover, some cancer tissues included a-1-antichymotrypsin-containing histiocytes in a stroma. It is known that histiocytes can pro-duce a-1-antichymotrypsin.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al . reported that cancer cells were more strongly positive for ACT than benign prostatic hyperplasia, resulting in a decreased free to total PSA ratio 21 . Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al reported that cancer cells were more strongly positive for ACT than benign prostatic hyperplasia, resulting in a decreased free to total PSA ratio. 21 Wu et al reported, from their analysis of cDNA sequence data, that the peptide backbone of prostatic ACT is identical to the protein derived from the liver, and thus may be functional as a protease inhibitor. 22 From our findings, ACT is mainly seen in normal duct and cancer cells.…”
Section: Discussionmentioning
confidence: 99%